Biosynthesis of molecular species of inositol, choline, serine, and ethanolamine glycerophospholipids in the bovine retina. - M I Aveldaño; S J Pasquare de Garcia; N G Bazán (Journal of Lipid Research, 1983)
The distribution of radioactivity among molecular species of inositol, choline, serine, and ethanolamine glycerophospholipids was studied in whole bovine retinas and in microsomes from retinas incubated with [3H]glycerol, [3H]inositol, or [3H]serine, in the presence and absence of propranolol. Most of the labeled glycerol was incorporated into docosahexaenoate-containing molecular species (hexaenes and dipolyunsaturates), which suggests that they are synthesized de novo. The largest accumulation of label in these species occurred in phosphatidylinositol, although they were only a minor component of this phospholipid. At short incubation times, these species, as well as monoenes and saturates, incorporated higher percentages of both [3H]glycerol and [3H]inositol than did the tetraenes. Labeling of tetraenes increased thereafter, suggesting that they are produced by acyl-exchange reactions from less unsaturated species. Propranolol was shown to stimulate phosphatidylinositol and polyphosphoinositide synthesis by preferentially enhancing first the labeling of monoenoic and saturated phosphatidylinositols, and subsequently tetraenes. Labeled glycerol was not redistributed among species of phosphatidylcholine with time. Propranolol inhibited the synthesis of monoenes and saturates to a greater extent than other species of phosphatidylcholine. The labeling of diglycerides was first inhibited, and then stimulated by propranolol; tetraenoic diglycerides were the major product accumulated. Propranolol stimulated [3H]serine incorporation into phosphatidylserine and phosphatidylethanolamine, with no alteration in distribution of radioactivity among species; [3H]glycerol incorporation in phosphatidylethanolamine was inhibited, and its incorporation into phosphatidylserine was stimulated. Labeled serine and glycerol were concentrated largely in docosahexaenoate-containing species of phosphatidylethanolamine and phosphatidylserine.